Modeling software measurement data. - Kitchenham, B.A (IEEE Transactions on software engineering)
This paper proposes a method for specifying models of software data sets in order to capture the definitions and relationships among software measures. We believe a method of defining software data sets is necessary to ensure that software data are trustworthy. Software companies introducing a measurement program need to establish procedures to collect and store trustworthy measurement data. Without appropriate definitions it is difficult to ensure data values are repeatable and comparable. Software metrics researchers need to maintain collections of software data sets. Such collections allow researchers to assess the generality of software engineering phenomena. Without appropriate safeguards, it is difficult to ensure that data from different sources are analyzed correctly. These issues imply the need for a standard method of specifying software data sets so they are fully documented and can be exchanged with confidence. We suggest our method of defining data sets can be used as such a standard. We present our proposed method in terms of a conceptual entity-relationship data model that allows complex software data sets to be modeled and their data values stored. The standard can, therefore, contribute both to the definition of a company measurement program and to the exchange of data sets among researchers